High-speed visualization of vortical cavitation using synchrotron radiation. (16th January 2018) - Karathanassis, Ioannis K.; Koukouvinis, Phoevos; Kontolatis, Efstathios; Lee, Zhilong; Wang, Jin; Mitroglou, Nicholas; Gavaises, Manolis
Abstract : High-speed X-ray phase-contrast imaging of the cavitating flow developing within an axisymmetric throttle orifice has been conducted using high-flux synchrotron radiation. A white X-ray beam with energy of 6 keV was utilized to visualize the highly turbulent flow at 67 890 frames per second with an exposure time of 347 ns. The working medium employed was commercial diesel fuel at flow conditions characterized by Reynolds and cavitation numbers in the range of 18 000–35 500 and 1.6–7.7, respectively. Appropriate post-processing of the obtained side-view radiographs enabled the detailed illustration of the interface topology of the arising vortical cavity. In addition, the visualization temporal and spatial resolution allowed the correlation of the prevailing flow conditions to the periodicity of cavitation onset and collapse, to the magnitude of the underlying vortical motion, as well as to the local turbulence intensity.